Why People with More Emotion Regulation Difficulties Made a More Deontological Judgment: The Role of Deontological Inclinations - Zhang, Lisong; Li, Zhongquan; Wu, Xiaoyuan; Zhang, Ziyuan (Frontiers in Psychology, 2017)
Previous studies have demonstrated the key role of emotion in moral judgment, and explored the relationship between emotion regulation and moral judgment. The present study investigated the influence of individual differences in emotion regulation difficulties on moral judgment. Study 1 examined whether individuals with high emotion regulation difficulties made a more deontological judgment. Study 2 explored the underlying mechanism using a process-dissociation approach, examining whether deontological inclinations and utilitarian inclinations separately or jointly accounted for the association. The results indicated that individuals with high emotion regulation difficulties rated the utilitarian actions less morally appropriate, and one’s deontological inclinations mediated the association between emotion regulation difficulties and moral judgment.